Ethnopharmacological study of medicinal plants indigenous knowledge about low back pain therapy in Sumatra, Indonesia - Ulfatun Nisa, Agus Triyono, Danang Ardiyanto, Fajar Novianto, Ulfa Fitriani, Wayan D. Miftakhul Jannah, Peristiwan R. Widhi Astana, Zuraida Zulkarnain (Journal of Applied Pharmaceutical Science, 2022)
Indonesians have had a close relationship with traditional herbal medicine for ages to maintain their health. As a common disease in the community, low back pain (LBP) is always considered for traditional healers in their practice. However, there are still insufficient data regarding the use of medicinal plants for LBP treatment. An ethnopharmacological study was conducted in Sumatra, Indonesia, to gain information on the empirical use of medicinal plants for LBP therapy among traditional healers. The information on the use of medicinal plants was gathered using semistructured questionnaires and interviews with traditional healers. The collected data were analyzed using several parameters such as family use value (FUV), use value (UV), and plant part used. A total of 90 traditional healers in Sumatra cited 68 plant species in 32 families that are used in their herbal formula for LBP treatment. They prefer to use leaves, roots, and barks than other parts of a plant. The calculation result of UV reveals that Kaempferia galanga is the most common plant used for LBP (0.04). Zingiberaceae was categorized as having the highest FUV. Datura metel was a toxic plant. The phytochemical and pharmacological screening of the indicated therapeutic plants should be investigated.
Keywords: Low back pain, medicinal plants, ethnopharmacology, Indonesia